PENGEMBANGAN TES DIAGNOSTIK THREE TIER MULTIPLE CHOICE BERBASIS GOOGLE FORMS UNTUK MENGIDENTIFIKASI MISKONSEPSI KPK FPB DI SD - Cahyani, Fitriana Kurnia; Surayanah, Surayanah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Misconceptions were found in the initial test at a rate of 38%. Misconceptions that are left unaddressed can continue to carry over and hinder students' understanding of interrelated advanced concepts. Therefore, a Three Tier Multiple Choice diagnostic test instrument based on Google Forms is needed to identify misconceptions about KPK and FPB in elementary schools more deeply.. The development model used is the Borg & Gall model with 10 stages. The developed instrument was validated by subject matter and instrument experts and tested on a small scale with 14 sixth-grade students at SDN Bungkal and on a large scale with 76 fifth- and sixth-grade students at SDN Bendogerit 1. The results showed that the instrument was highly valid, with a score of 100% from subject matter experts and 88% from instrument experts. The instrument was also considered highly practical by teachers and students. The final results of the instrument showed that 21 questions were valid with a reliability score of 0.875. It had a moderate difficulty level with a score of 0.50 in tier 1 and 0.48 in tier 2. The discriminating power was rated as good with an average of 0.45 in tier 1 and 0.43 in tier 2. The quality of distractors on the final instrument was also fully active. The Google Forms-based Three Tier Multiple Choice (TTMC) diagnostic test was declared effective in identifying misconceptions with a significance level of <0.001. Cases of misconceptions were identified four types of misconceptions that emerged, namely 100% conceptual misconceptions, 62% calculation misconceptions, 24% strategy misconceptions, and 24% systematic misconceptions.